How Much Veil Is Too Much Veil: On the Constitutionality and Advisability of Face Veil Bans for German Public School Students. Issue 6 (1st November 2017) - Braun, Kerstin
Abstract : With increasing cultural and religious diversity in Germany, a debate has emerged over the extent and limits of religious freedom in day-to-day life. While much controversy arose over whether public school teachers have the right to wear Islamic head coverings, students as private individuals are free to wear a headscarf at school if they wish. Yet, recent school and administrative court decisions suggest that the situation is different for students who wear niqab and Islamic face veils rather than just head veils. This Article contemplates whether niqab-wearing students can be expelled from public school under current German law. In addition, this Article addresses the constitutionality of law reform in this area especially considering the European Court of Human Rights' jurisprudence in the French context. The Article subsequently contemplates the advisability of such law reform while also drawing on the experiences of countries which have already enacted so-called burqa bans. As many countries are currently in the process of considering face veil bans, this Article may have relevance beyond the German context.